Caregiver Preferences for Three-Dimensional Printed or Augmented Reality Craniosynostosis Skull Models: A Cross-Sectional Survey. Issue 1 (12th January 2022) - Chen, Jonlin; Kumar, Sahana; Shallal, Christopher; Leo, Kirby T.; Girard, Alisa; Bai, Yunong; Li, Yukang; Jackson, Eric M.; Cohen, Alan R.; Yang, Robin
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Recent advances in three-dimensional (3D) printing and augmented reality (AR) have expanded anatomical modeling possibilities for caregiver craniosynostosis education. The purpose of this study is to characterize caregiver preferences regarding these visual models and determine the impact of these models on caregiver understanding of craniosynostosis. Methods: The authors constructed 3D-printed and AR craniosynostosis models, which were randomly presented in a cross-sectional survey. Caregivers rated each model's utility in learning about craniosynostosis, learning about skull anatomy, viewing an abnormal head shape, easing anxiety, and increasing trust in the surgeon in comparison to a two-dimensional (2D) diagram. Furthermore, caregivers were asked to identify the fused suture on each model and indicate their preference for generic versus patient-specific models. Results: A total of 412 craniosynostosis caregivers completed the survey (mean age 33 years, 56% Caucasian, 51% male). Caregivers preferred interactive, patient-specific 3D-printed or AR models over 2D diagrams (mean score difference 3D-printed to 2D: 0.16, P  < 0.05; mean score difference AR to 2D: 0.17, P  < 0.01) for learning about craniosynostosis, with no significant difference in preference between 3D-printed and AR models. Caregiver detection accuracy of the fused suture on the sagittal model was 19% higher with the 3D-printed model than with the AR model ( P  < 0.05) and 17% higher with the 3D-printed model than with the 2D diagram ( P  < 0.05). Conclusions: Our findings indicate that craniosynostosis caregivers prefer 3D-printed or AR models over 2D diagrams in learning about craniosynostosis. Future craniosynostosis skull models with increased user interactivity and patient-specific components can better suit caregiver preferences.